Political Intertheology - Di Blasi, Luca (Political theology, 2024)
The following paper introduces the concept of political intertheology as a post-secular counterpart to Carl Schmitt's notion of political theology. It elaborates this concept by examining two interpretations of the New Testament narrative regarding the choice between Jesus and Barabbas. Both interpretations revolve around the relationship between Christianity and Judaism. The first, anti-antisemitic reading, emphasizes the identity between Jesus and Barabbas. The second, anti-anti-Christian interpretation, intensifies the political-theological antagonism. This article proposes a third, guilt-political interpretation. This perspective enables us to acknowledge both the inevitability of the distinction between Christians and what they perceived as Jews, and the fact that a politico-intertheological intensification (the accusation against the Jews of demanding the crucifixion of Jesus) was not inevitable. Understanding how it unfolded facilitates overcoming this fateful accusation at its core, without succumbing to a new accusation (against early Christians) and thereby replacing anti-Judaism with potential anti-Christian sentiment.